IMPROVING STUDENT COMPETENCE THROUGH LEARNING MANAGEMENT OUTCOME BASED EDUCATION - Husna, Khotimatul; Mundiri, Akmal; Agus R, Abu Hasan (PEDAGOGIK : JURNAL PENDIDIKAN, 2023)
The era of the industrial revolution 4.0 really needs human resources who have excellence in the fields of communication and knowledge, where higher education as a place for building student character has an important role in improving the quality and competence of students in the results-based domain. This OBE-based learning can be the main way for students to develop the competencies that each student has that they cannot express when they are students. This competence and results-based learning does not only focus on learning using methods but also in conducting field work practices. Writing this scientific paper has a very significant goal in realizing student competency in improving the quality of results-based learning. The research approach used is a qualitative approach with a case study type. In order to obtain data, researchers used observation and interview techniques. The results of the study show that the management of learning based on outcome base education in order to improve quality and competence is carried out in the form of; Internships and work practices, serving students, teaching campuses and student exchanges.